2023
DOI: 10.2174/1573409919666230103144045
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided Design and Optimization of small Molecules as Pancreatic Lipase Inhibitors using Pharmacophore, 3D-QSAR, Molecular Docking, and Molecular Dynamics Simulation Studies

Abstract: Background: Obesity has now become a global issue due to the increase in the population of obese people. It also substantially impacts the individual's social, financial, and psychological well-being, which may contribute to depression. Being overweight induces many metabolic and chronic disorders, urging many researchers to focus on developing the drug for obesity treatment. Pancreatic lipase inhibitors and natural product/compound-derived pancreatic lipase inhibitors have recently received much attention bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…This indicated that isovitexin induced a change in PL compactness and caused the structure of the enzyme to become swollen and loose. Consequently, there was an increase in its cavity and a change in PL conformation, which was consistent with the results shown in CD spectra above [70]. As an indicator of the surface properties of macromolecules, SASA can be used to determine the surface area of PL in contact with isovitexin.…”
Section: Discussionsupporting
confidence: 87%
“…This indicated that isovitexin induced a change in PL compactness and caused the structure of the enzyme to become swollen and loose. Consequently, there was an increase in its cavity and a change in PL conformation, which was consistent with the results shown in CD spectra above [70]. As an indicator of the surface properties of macromolecules, SASA can be used to determine the surface area of PL in contact with isovitexin.…”
Section: Discussionsupporting
confidence: 87%